Metacognitive Skills Assessment in Research-Proposal Writing (MSARPW) in the Indonesian University Context: Scale Development and Validation Using Multidimensional Item Response Models - Bahrul Hayat; Wardani Rahayu; Muhammad Dwirifqi Kharisma Putra; Iva Sarifah; Tina Deviana; Valendra Granitha Shandika Puri; Khairunesa Isa (Fakultas Psikologi UIN Syarif Hidayatullah Jakarta, 2023)
This study aimed to develop the Metacognitive Skills Assessment in a Research Proposal Writing Context (MSARPW), a multidimensional measure, based on student perspectives, for assessing metacognitive skills in thesis writing, and assess the instrument’s psychometric properties using item factor analysis (IFA) and multidimensional item response models. The 40-item MSARPW was administered to 602 Indonesian university students (Mage = 25.254 SDage = 6.854). The IFA showed that the two-dimensional factor structure of MSARPW was satisfactory; however, only 24 of the 40 items were found to fit the model. Multidimensional graded response models (MGRM) were applied to the subsequent 24-item MSARPW, which showed that one item (Item 4) did not satisfy the criteria. The estimated reliabilities of each subscale showed that the 23-item MSARPW has good internal consistency (0.891 and 0.902). To conclude, the 23-item MSARPW appears to be a valid and reliable tool for assessing metacognitive skills in the context of research-proposal writing among Indonesian university students.